Evaluasi Program Optimalisasi Pengolahan dan Pemasaran Hasil Perikanan Perspektif Gender di Kota Ternate - Misrina (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
Abstract This article describes the evaluation of the implementation of fisheries product processing and marketing program in Ternate City. This research uses a qualitative approach with in-depth interviews with informants selected based on purposive sampling. The theory used to evaluate is the CIPP model (Contex, Input, Process, Product). The results of the research found problems in the program implementation process that fishermen's wives did not benefit from various activities so it can be concluded that the program must be reviewed so that the beneficiaries can be expanded, especially fishermen's wives who are still living in poverty. The novelty of this research is that the value of justice for women is at the core of this evaluation. This program should provide help to coastal women who live difficult lives during seasonal changes. The implication of this research is that the sustainability of fisheries product processing programs should prioritize the principle of justice for poor coastal communities. Program Evaluation, Gender Justice, Fisheries Product Processing Market.